2018
DOI: 10.3390/nu10081091
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Association between Dietary Fiber Intake and Hypertension among U.S. Adults Using 2017 American College of Cardiology/American Heart Association Blood Pressure Guidelines: NHANES 2007–2014

Abstract: This study aimed to explore the association between dietary fiber intake and hypertension risk using 2017 American College of Cardiology/American Heart Association Blood Pressure Guidelines. Data from the National Health and Nutrition Examination Survey 2007–2014 were used in this study. Dietary fiber data were obtained through two 24-h dietary recall interviews. Hypertension was defined as systolic blood pressure (SBP) ≥ 130 mmHg or diastolic blood pressure (DBP) ≥ 80 mmHg or treatment with hypertensive medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 24 publications
4
32
0
3
Order By: Relevance
“…In addition to coffee and caffeine intake from coffee, we investigated some potential confounding factors, which included: age (60-70 years, 70-80 years, and ≥80 years), gender (male and female), race (Mexican American, other Hispanic, Non-Hispanic White, Non-Hispanic Black and other races), educational level (below high school, high school and above high school), marital status (married/living with partner and widowed/divorced/separated/never married), poverty-income ratio (≤0.99 and ≥1), body mass index (BMI) (normal: <25 kg/m 2 , overweight: 25 to <30 kg/m 2 , obese: ≥30 kg/m 2 ), drinking (having at least 12 alcohol drinks per year or not) and smoking status (never: never smoked or smoked <100 cigarettes in life, former: smoked ≥100 cigarettes in life and currently no longer smoking and current: smoked ≥100 cigarettes in life and currently smoking) [45,46]. Total energy intake was obtained from the 24-hour dietary recall.…”
Section: Covariatesmentioning
confidence: 99%
“…In addition to coffee and caffeine intake from coffee, we investigated some potential confounding factors, which included: age (60-70 years, 70-80 years, and ≥80 years), gender (male and female), race (Mexican American, other Hispanic, Non-Hispanic White, Non-Hispanic Black and other races), educational level (below high school, high school and above high school), marital status (married/living with partner and widowed/divorced/separated/never married), poverty-income ratio (≤0.99 and ≥1), body mass index (BMI) (normal: <25 kg/m 2 , overweight: 25 to <30 kg/m 2 , obese: ≥30 kg/m 2 ), drinking (having at least 12 alcohol drinks per year or not) and smoking status (never: never smoked or smoked <100 cigarettes in life, former: smoked ≥100 cigarettes in life and currently no longer smoking and current: smoked ≥100 cigarettes in life and currently smoking) [45,46]. Total energy intake was obtained from the 24-hour dietary recall.…”
Section: Covariatesmentioning
confidence: 99%
“…The Nurses’ Health Study (41,541 US women; 4 years) observed that women consuming <10 g fiber/day had a 109% greater risk of elevated BP compared to women consuming ≥25 g fiber/day [186]. A NHANES analysis of data between 2007–2014 (18,433 US adults; ≥18 years) showed that the intakes of cereal and vegetable fibers were associated with significantly lower hypertension risk by 18–20%, but fruit fiber was insignificantly associated with a 14% lower risk of hypertension, which is inconsistent with previous studies and potentially due to a younger demographic and the methodology used [187]. The consumption of whole fruits and fruit fiber lowers the risk of hypertension and reduces BP more effectively than vegetables, especially in middle aged or older adults.…”
Section: Emerging Health Benefits Associated With Whole Fruits Andmentioning
confidence: 99%
“…The following covariates were included in this study: age, gender, race, marital status, education level, annual household income, smoking status, alcohol consumption status, work activity, recreational activity, body mass index (BMI), hypertension, diabetes, coronary heart disease, and energy intake. The classifications of covariates were based on our previous studies [13,14,37] and are shown in Table S1.…”
Section: Covariatesmentioning
confidence: 99%